POTENSI WAKAF UANG DIGITAL (FINANCIAL TECHNOLOGI SYARIAH) DALAM MEMBANGUN KESEJAHTERAAN EKONOMI MASYARAKAT - A.Fahmi Zakariya; Nur Hidayatul Istiqomah; Bayu Aji (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
Cash waqf has played an important role as one of the new Islamic fiscal instruments in the economy. Cash waqf has two functions as a means of worship and the achievement of social welfare. Returns from cash waqf management can be used as an instrument in poverty alleviation programs through the social security system. The social security system using cash waqf will be able to help poverty alleviation programs carried out by the government through community empowerment programs. This study aims to determine the potential aspects of financial technology related to waqf in finding cash waqf in Indonesia. Cash waqf in Indonesia is very potential, if all aspects are maximized, including technological tools in socializing the urgency and benefits of waqf for economic, social and religious progress of the community. The method used in this paper uses a qualitative method with a literature approach that uses supporting data that is analyzed descriptively. The findings in this study explain the opportunities for digital cash waqf in the progress of the revaluation of industry 4.0 in Indonesia. The spirit of the Muslim community in conducting cash waqf must be managed with technological conveniences. The existence of digital cash waqf through Fintech can make it easier for waqf to do money waqf, so from this facility the potential for cash waqf can be collected and and can be managed for productive waqf activities in building community welfare.